Rethinking police education in the United States. (4th May 2019) - Cordner, Gary
ABSTRACT: Higher education for police in the United States began as police science and police administration in the early-to-middle 1900s but morphed into criminal justice starting in the 1960s, continuing in that mold to the present. This paper examines curricula at a handful of universities to provide a snapshot of U.S. police education today, illustrating that modern criminal justice programs do not focus very much on police at either the undergraduate or graduate level. The paper then considers alternative models that could provide students a more in-depth encounter with the now-robust policing body of knowledge, something that barely existed 50 years ago but could, at this point, serve as the foundation for a respectable and relevant academic and professional education.